Children of the postcolony Filipino intellectuals and decolonization, 1946-1972 - Veric, Charlie S. (Charlie Samuya) (Ateneo de Manila University Press, 2020)
Writing against historical forgetting, Charlie Samuya Veric reconstructs the foundations of Filipino postcolonial thought following Philippine independence from the United States in 1946. On the one hand, he narrates the rise of postcolonial knowledge after the formal birth of the nation. On the other, he examines the ideas of the first generation of intellectuals who came of age after independence—Edith L. Tiempo, Fernando Zobel, Bienvenido L. Lumbera, E. San Juan, Jr., and Jose Maria Sison—whose penetrating insights into literary formalism, modern art, vernacular tradition, subaltern internationalism, and mass revolution constitute key cultural archives of postcolonial knowledge production. Original and provocative, Children of the Postcolony illuminates Filipino decolonization and argues for the vitality of its still unrealized dreamworld.-- BAck cover.